Process Intensification for Recombinant Marburg Virus Glycoprotein Production Using Drosophila S2 Cells - Sven Göbel; Ludwig Mayerlen; Isabelle Yazel Eiser; Lisa Fichtmueller; David Clements; Udo Reichl; Yvonne Genzel; AxelT. Lehrer (Engineering in Life Sciences)
ABSTRACT Marburg marburgvirus (MARV) is a highly virulent human pathogen with limited therapeutic options. Recombinant MARV glycoprotein (GP) produced in Drosophila Schneider 2 (S2) cells has been extensively investigated as potential vaccine antigen with promising efficacy demonstrated in nonhuman primate models. However, the existing production process for MARV‐GP involving static batch cell cultures with limited scalability and process control show lower than desirable yields. Here, we assessed various process intensification strategies in single‐use orbital shaken bioreactors (OSBs) or rocking bioreactors (WAVE) and report maximum viable cell concentrations (VCCs) of 31.6 × 106 cells/mL in batch, 69.5 × 106 cells/mL in fed‐batch (FB), and up to 210.0 × 106 cells/mL in perfusion mode. By changing from a glucose‐only feed to a CellBoost5 feed, MARV‐GP yields were increased by over two‐fold. Implementation of perfusion cultures achieved a peak MARV‐GP concentration of 57.4 mg/L and a 540% higher space‐time yield compared to the FB process in the 50 L WAVE system. However, maximum cell‐specific productivities were achieved at a VCC of 85 × 106 cells/mL and decreased with increasing cell concentrations. Glycoanalysis revealed a uniform paucimannosidic N‐glycan profile, predominantly α‐1,6‐core‐fucosylated Man3F (F(6)M3) structures, across all production modes. Notably, transitioning pH control from CO2 to phosphoric acid shifted glycan profiles toward higher mannose forms, highlighting the influence of culture conditions on glycosylation.